Main areas of the work of «third sector» organizations under the conditions of the martial law - Vitkovska, Inna (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2022)
The article is devoted to the analysis of the main areas of work of «third sector» organizations in the conditions of martial law in Ukraine and the determination of the problems they face in their activities. Based on the secondary analysis of statistical data, it was found that the number of non-governmental and charitable organizations in Ukraine is growing year by year, which is one of the signs of the development of civil society. During 2022, 96,500 non-governmental and 19,112 charitable organizations were registered in Ukraine. The author's analysis of the websites of non-governmental and charitable organizations and the results of sociological research allowed us to conclude that the main trends and areas of work of «third sector» organizations include: an increase in the number of non-governmental, charitable organizations, fundraising platforms and volunteer headquarters, which are focused on helping the army, internally displaced persons, centers for displaced persons and victims of war, payment of monetary aid and assistance with evacuation to safe places in Ukraine or abroad; increase in financing of non-governmental and charitable organizations at the expense of international donor organizations; mass spread of voluntary and charitable practices among the population of Ukraine and the growth of trust in the activities of «third sector» organizations. Based on the analysis of in-depth interviews with the heads of non-governmental and charitable organizations of the Kharkiv, Sumy, Poltava and Donetsk regions, which were conducted within the framework of the research topic of the Sociology of Management and Social Work Department «Actual trends in the management of social services» in November 2022, we can to conclude that the most urgent problems of these organizations in the conditions of martial law are continuation of military operations; creation of safe working conditions for employees and beneficiaries during air alarms; property damage; personnel turnover; lack of a sufficient number of specialists and a long search for narrow specialists (lawyer, psychologist, social worker, crisis consultant); excessive load on one employee; many beneficiaries; a long wait for the collection of funds from donors for the implementation of aid programs; absence of a state component in the financing of the organization's projects and the social order for social services provided by the organization; lack of technical equipment, etc.